Congenital Insensitivity to Pain with Anhidrosis (CIPA) Manifested with Chronic Osteomyelitis; A Case Report - KÜÇÜKDURMAZ, FATİH; KÜÇÜKDURMAZ, FATİH; Imren, Yunus; Uruc, Vedat; Sen, Cengiz (My University, 2015)
Chronic osteomyelitis is a very rare entity among children. Also congenital insen-sitivity to pain with anhidrosis (CIPA) is a very rare autosomal-recessive disease of the nervous system which is one of the hereditary sensory and autonomic neuropathies (HSAN). Loss of pain, fever due to anhidrosis, recurrent fractures, chronic osteomyelitis, mental retardation, self mutilation, wound ulcers can be seen. We present a 10-year-old boy with loss of generalized pain sensation, chronic osteomyelitis on his right distal femur, bilateral corneal opacities, and decreased mental capacity.